2020
DOI: 10.1002/hbe2.190
|View full text |Cite
|
Sign up to set email alerts
|

The realism paradox: Realism can act as a form of signaling despite being associated with cognitive load

Abstract: Realistic graphics have been found to result in a worse learning performance than schematic visualizations. These negative results of realism are usually explained by assuming that realistic visualizations induce more cognitive load. Therefore, realism has been linked to the facet of extraneous cognitive load in the model of cognitive load theory. However, recent results indicate that realism may be used to good advantage when it is utilized only in selected parts of visualizations. We tested the hypothesis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 48 publications
0
60
0
Order By: Relevance
“…This approach follows previous research in the field of learning (e.g., Prisacari & Danielson, 2017). On the next page, participants were asked to indicate whether they were strongly distracted during the learning phase and whether there had been major technical issues during the learning phase (taken from Skulmowski & Rey, 2020b). The laboratory experiment used SoSci Survey (Version 3.2.03‐i; Leiner, 2019; https://www.soscisurvey.de).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This approach follows previous research in the field of learning (e.g., Prisacari & Danielson, 2017). On the next page, participants were asked to indicate whether they were strongly distracted during the learning phase and whether there had been major technical issues during the learning phase (taken from Skulmowski & Rey, 2020b). The laboratory experiment used SoSci Survey (Version 3.2.03‐i; Leiner, 2019; https://www.soscisurvey.de).…”
Section: Methodsmentioning
confidence: 99%
“…This combination of realistic and schematic content improved the learning performance of routes compared to fully realistic and fully schematic virtual displays of the routes in question (Lokka & Çöltekin, 2019). Building on this result, Skulmowski and Rey (2020b) found that in a combined presentation of realistic and schematic visualizations, retention performance was higher for the realistic portions of the learning materials. As presented above, earlier studies in the field of anatomy learning suggest benefits of learning with more realistic and detailed visualizations for specific tests (e.g., Dwyer Jr, 1967).…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations